Identifikasi Peptida Hidrolisat Protein Maggot Lalat Tentara Hitam (Black Soldier Fly) - Syadza Syahida Zahra; Hanifa Rahma (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Maggot BSF (Hermetia illucens) is known as an alternative protein source with high protein content, making it a promising candidate for applications in the food and pharmaceutical industries. This study aimed to determine the highest yield produced from enzymatic hydrolysis using alkalase, pepsin, and trypsin, as well as to identify the resulting peptides using the SDS-PAGE method. The research procedures included dry maggot preparation, defatting, protein isolation, enzymatic hydrolysis, and peptide identification. The results showed that alkalase produced the highest hydrolysate yield at 23.78%, compared to pepsin and trypsin. SDS-PAGE analysis indicated differences in protein bands between samples before hydrolysis (8–270 kDa) and after hydrolysis, with molecular weights of approximately 30 kDa (HPEA), 45 kDa (HPEP), and 20 kDa (HPET), respectively. These results confirmed that the hydrolysis process successfully broke down the proteins into lower molecular weight peptides. In conclusion, alkalase, pepsin, and trypsin were proven effective in hydrolyzing maggot protein into peptides with lower molecular weights, which have potential to be developed as bioactive compounds. Abstrak. Maggot BSF (Hermetia illucens) diketahui merupakan sumber protein alternatif dengan kandungan protein tinggi yang berpotensi untuk diaplikasikan dalam bidang pangan dan farmasi. Penelitian ini bertujuan untuk menentukan rendemen tertinggi yang dihasilkan dari proses hidrolisis menggunakan enzim alkalase, pepsin, dan tripsin, serta mengidentifikasi peptida hasil hidrolisis menggunakan metode SDS-PAGE. Tahapan penelitian meliputi preparasi maggot kering, defatting, isolasi protein, hidrolisis protein secara enzimatik, dan identifikasi peptida. Hasil menunjukkan bahwa enzim alkalase menghasilkan rendemen hidrolisat tertinggi, yaitu sebesar 23,78%, dibandingkan dengan enzim pepsin dan tripsin. Analisis SDS-PAGE menunjukkan perubahan pita protein antara sampel sebelum hidrolisis (8–270 kDa) dan sesudah hidrolisis, masing-masing sebesar ±30 kDa (HPEA), ±45 kDa (HPEP), dan ±20 kDa (HPET). Hasil ini menunjukkan bahwa proses hidrolisis berhasil memecah protein menjadi peptida dengan bobot molekul yang lebih rendah. Hasil akhir menyatakan bahwa enzim alkalase, pepsin dan tripsin terbukti berhasil memecah protein menjadi peptida dengan bobot molekul yang lebih rendah dan berpotensi untuk dikembangkan sebagai senyawa bioaktif.